2021
DOI: 10.1002/aur.2499
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal infection and risk for autism in offspring: A meta‐analysis

Abstract: While prenatal maternal infection has received attention as a preventable and treatable risk factor for autism, findings have been inconsistent. This paper presents the results of a meta‐analysis to determine whether the weight of the evidence supports such an association. Studies with a categorical diagnosis of autism as the outcome and an assessment of its association with prenatal maternal infection or fever (or the data necessary to compute this association) were included. A total of 36 studies met these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 81 publications
(92 reference statements)
2
26
0
Order By: Relevance
“…Many aspects of our data are compatible with this concept. For example, our finding that trans-and cis-diagnostic risk variants are enriched at sites epigenetically activated by delayed T cell responses to a wide range of pro-inflammatory cytokine stimuli seems consistent with the epidemiological finding that increased risk of multiple psychiatric disorders is found following a wide range of different infections 12,28,29,64,65 . Atypical T cell phenotypes could conceivably have effects on the brain by at least two broad routes: via stimulus-driven T cell activation and via developmental pathways (Figure 5).…”
Section: Discussionsupporting
confidence: 88%
“…Many aspects of our data are compatible with this concept. For example, our finding that trans-and cis-diagnostic risk variants are enriched at sites epigenetically activated by delayed T cell responses to a wide range of pro-inflammatory cytokine stimuli seems consistent with the epidemiological finding that increased risk of multiple psychiatric disorders is found following a wide range of different infections 12,28,29,64,65 . Atypical T cell phenotypes could conceivably have effects on the brain by at least two broad routes: via stimulus-driven T cell activation and via developmental pathways (Figure 5).…”
Section: Discussionsupporting
confidence: 88%
“…Associations between ASD and prenatal infection with specific pathogens, such as rubella and cytomegalovirus, have been repeatedly reported ( 153 ). Meta-analyses revealed a mild but significant increase in the risk of ASD in children of mothers who experienced infection during pregnancy, regardless of the pathogen ( 154 , 155 ). One study estimated that maternal infection accounts for 12–17% of ASD cases ( 155 ).…”
Section: Maternal Immune Activationmentioning
confidence: 99%
“…Meta-analyses revealed a mild but significant increase in the risk of ASD in children of mothers who experienced infection during pregnancy, regardless of the pathogen ( 154 , 155 ). One study estimated that maternal infection accounts for 12–17% of ASD cases ( 155 ). The risk of ASD appears to correlate with the severity of maternal infection, in which the risk was further elevated when mothers required hospitalization because of the infection ( 154 ).…”
Section: Maternal Immune Activationmentioning
confidence: 99%
“…The use of antimicrobial therapy during pregnancy has been associated with various unwanted outcomes in the offspring, including cerebral palsy, epilepsy, immune system alterations, childhood asthma, changes in gut microbiota, obesity, and functional impairments (24). The effect of antimicrobial use during pregnancy on ASD risk is not yet clear: while some studies have reported that the use of antimicrobials during pregnancy is associated with an increased risk of ASD (17,21,(30)(31)(32)(33)(34), other studies did not find such association (35). Therefore, the objective of this study was to investigate the association between the use of antimicrobials during pregnancy and the risk of ASD in the offspring.…”
Section: Introductionmentioning
confidence: 99%